Pelatihan Seni Peran Pada Naskah Anak “Sawunggaling Punya Cita-Cita” Karya Arif Rofiq Untuk Meningkatkan Kreativitas Siswa SD Muhammadiyah 4 Pucang Surabaya - Moh Mujib Alfirdaus; Arif Rofiq; Bramantijo Bramantijo (Sekolah Tinggi Kesenian Wilwatikta (STKW) Surabaya, 2023)
This community service aims to improve the abilities of Muhammadiyah 4 Pucang Elementary School students in Surabaya in processing artistic creativity through acting. The material provided is studying and imitating characters in children's story texts who have local history competence and are socio-cultural. The learning model is role-playing based on children's games or role-playing by inviting students to imitate cute animal movements, traditional games, and character dialogues in children's story scripts that have local content and aspects of populist history. The basic reason for carrying out this activity is the lack of knowledge and experience of students in cultivating creativity through knowledge of children's script stories that are local to regional culture. The hope is to provide space for creativity to every student while at the same time strengthening the existence of regional arts and culture in children as the next generation of the nation. The steps are taken by providing role training to the characters through concentration, emotional memory, dramatic behavior, character building, observation, and rhythm. The result of this training is a form of children's drama performance. This Community Service activity through acting training on a children's script entitled Sawunggaling Has Ideals by Muhammadiyah Elementary School students is to foster creativity and interest in art in children through children's drama performances that have local historical and socio-cultural values.